Modelling the Efficiency of Paddy Production in Peninsular Malaysia Using Principal Component Analysis and Data Envelopment Analysis (PCA-DEA) - Aisyah Ismail; Zalina Zahid; Siti Aida Sheikh Hussin; Siti Shaliza Mohd Khairi (International Journal of Supply Chain Management, 2018)
Although the current paddy production in Peninsular Malaysia shows a satisfying self-sufficiency level, the countrys annual rough paddy production, however, will still have to increase over the next 10 years to sustain up with the local population growth and the growing demand level for this staple food. Thus, immediate action needs to be done to evaluate the efficiency of paddy production, so that the information obtained can help the government to come out with strategies to maximize the outputs with the current existing inputs. The objective of this study is to measure the efficiency of paddy production of 11 states in Peninsular Malaysia using a hybrid of Principal Component Analysis and Data Envelopment Analysis. The variables used as inputs include planted paddy area, number of rice farmers, amount of seeds usage and total budget allocation whereas the variables used as outputs cover paddy output, rice output and rice income. As the input and output variables are highly correlated, this study proposes the combination of Principal Component Analysis (PCA) and Data Envelopment Analysis (DEA) approaches to reduce the data dimensionality problem instead of eliminating the variables with multicollinearity problem from the analysis. PCA is applied separately on both sides of all inputs and all outputs, resulting in one principal component (PC) to represent the input and one PC to represent the output side. Both PCs were found to contribute greater than 70% of the data variation. The results from output-oriented DEA model under variable return to scale (VRS) indicate that Kedah is the most efficient state in producing the paddy output, leaving the rest of states with average efficiency scores ranging from 0.745 to 0.998. Further results show that Kelantan, Terengganu and Pahang were placed at the lowest three states in terms of efficiency levels. There is a need for the government to pay extra attention on these states in bringing off the significant factors that may disrupt the functioning of efficient paddy production.